A qualitative study on the influence of organisational readiness and socio-technical alignment of AI integration within the downstream oil and gas supply chain risk management - Wolf-Piggott, Brendon Bernard (University of Pretoria, 2026)
Mini Dissertation (MBA)--University of Pretoria, 2025.